The tricky effects of TROP2 in lung cancer: from clinical practice back to fundamental investigations - Liu, Renwang; Li, Mingbiao; Gao, Penghu; Li, Xuanguang; Zhang, Zihe; Chen, Jun (Frontiers in Oncology, 2025)
TROP2, a transmembrane glycoprotein, is overexpressed and plays pivotal roles in diverse epithelial tumors. The differential expression of TROP2 between cancer and normal tissues offers distinct advantages in developing drugs targeting it. Thus, TROP2-targeted antibody-drug conjugates (ADCs), including datopotamab deruxtecan and sacituzumab govitecan, present considerable efficacy and safety in multiple cancers. However, in lung cancer, the application of TROP2-targeted ADCs has many limitations and challenges. The current clinical trials have not achieved encouraging results yet. Meanwhile, the expression of TROP2 in lung cancer remains ambiguous, let alone its biological effects and underlying mechanism. The complex features and limited research may slow down the development of TROP2-targeted ADCs in lung cancer. Therefore, we comprehensively reviewed the literature on TROP2 in lung cancer, extending back to basic research from clinical trials. We also combined several preliminary bioinformatics analyses in this review and intended to find some research directions on breaking through these limitations.